Sintesis dan Karakterisasi Carbon Nanodots dengan Metode Microwave Assisted Extraction: Synthesis and Characterization of Carbon Nanodots with Microwave Assisted Extraction - Mentik Hulupi; Haryadi; Nabila Sofiyani; Rizka Amalia Nuriana; Retno Indarti; Fauzi Abdilah (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2022)
Carbon nanodots (CNDs) is one of the carbon nanoparticles that are environmentally friendly, non-toxic, and have optical properties. The aim of this study was to synthesize CNDs from ascorbic acid as a precursor using the Microwave Assisted Extraction method. method. Best results are obtained at 4 minutes of heating and 500W of power. The synthesized CNDs solution showed a blue color under 365 nm UV light. The measurement results with UV Vis spectrophotometer showed the maximum wavelength at 341.5 nm with an energy gap of 5.57 eV. The results of the Fourier transform infrared spectroscopy (FTIR) analysis show that CNDs have the -OH (hydroxyl) functional group at a wave number of 3354.61 cm-1 and C=O functional group at a wave number of 1633.09 cm-1. Characterization results using High resolution transmission electron microscopy (HRTEM) showed that CNDs were spherical in shape with a particle size range of 2.54-9.48 nm.